H-MRS Correlates of Deep TMS in Schizophrenia: Insights From a Randomized Sham-Controlled Study on Negative Symptoms - Gulesh Kumar; Nishant Goyal; Aniruddha Mukherjee (BJPsych Open, 2025)
Aims: Negative symptoms of schizophrenia are disabling and often show inadequate response to antipsychotic treatment. Dysfunction in cortical regions such as the anterior cingulate cortex (ACC) and medial prefrontal cortex (mPFC) has been implicated in these symptoms. While repetitive transcranial magnetic stimulation (rTMS) has shown efficacy, deep transcranial magnetic stimulation (dTMS) offers the advantage of targeting deeper brain structures.